Analisis Pendekatan Berdiferensiasi untuk Meningkatkan Keaktifan Peserta Didik pada Materi ASEAN di Sekolah Dasar - Wahyudi Kiswah; Adrias Adrias; Salmaini Safitri Syam (Pusat Riset dan Inovasi Nasional, 2025)
The Differentiated Approach is an approach that emphasizes the diverse learning styles of learners. The research aims to examine how a differentiated approach can increase students' learning activeness. Through the literature review method by relying on references that discuss the same topic in previous studies, it is expected to be able to increase activeness in students, especially in ASEAN material in social studies learning in elementary schools by focusing on the Cooperative Learning model, it is hoped that this model can provide enthusiasm to be active in students in the learning process. The results obtained prove that learning social studies in elementary school on ASEAN material using Cooperative Learning learning models can significantly increase student activeness in following learning.